Evolution of competitive ability and the response to nutrient availability: a resurrection study with the calcareous grassland herb, Leontodon hispidus - Pascal Karitter; Emma Corvers; Marie Karrenbauer; Martí March-Salas; Bojana Stojanova; Andreas Ensslin; Robert Rauschkolb; Sandrine Godefroid; J. F. Scheepens (Oecologia, 2025)
Rapid environmental changes across Europe include warmer and increasingly variable temperatures, changes in soil nutrient availability, and pollinator decline. These abiotic and biotic changes can affect natural plant populations and force them to optimize resource use against competitors. To date, the evolution of competitive ability in the context of changes in nutrient availability remains understudied. In this study, we investigated whether the common calcareous grassland herb Leontodon hispidus recently evolved its competitive ability and response to nutrient availability. We compared ancestors sampled in 1995 and descendants sampled in 2018 and applied a competition treatment in combination with weekly nutrient treatments (no fertilizer, nitrogen, phosphorus, and both). We found evidence for evolution of increased competitive ability, with descendants producing more vegetative biomass than ancestors when grown under competition. Furthermore, supplementing nutrients (especially N) reduced differences in competitive ability between ancestors and descendants, suggesting that nutrients are a limiting factor in interspecific competition, which could be linked to the decreasing nitrogen emissions into the atmosphere since the 1990s. Our study demonstrates rapid contemporary evolution of competitive ability, but also the complexity of the underlying processes of contemporary evolution, and sheds light on the importance of understudied potential selection agents such as nutrient availability.

Combining the resurrection approach with transplant experiments to investigate adaptation of plant populations to environmental change - Pascal Karitter; Martí March-Salas; Andreas Ensslin; Robert Rauschkolb; Sandrine Godefroid; J.F. Scheepens (Perspectives in Plant Ecology, Evolution and Systematics, 2024)

High phenotypic variation found within the offspring of each mother tree in Fagus sylvatica regardless of the environment or source population - Jonas Schmeddes; Lena Muffler; Adrià Barbeta; Ilka Beil; Andreas Bolte; Stefanie Holm; Pascal Karitter; Marcin Klisz; Magnus Löf; Manuel Nicolas; Josep Peñuelas; Yann Vitasse; et al. (Global Ecology and Biogeography, 2024)
Aim Climate change challenges temperate forest trees by increasingly irregular precipitation and rising temperatures. Due to long generation cycles, trees cannot quickly adapt genetically. Hence, the persistence of tree populations in the face of ongoing climate change depends largely on phenotypic variation, that is the capability of a genotype to express variable phenotypes under different environmental conditions, known as plasticity. We aimed to quantify phenotypic variation of central Europe's naturally dominant forest tree across various intraspecific scales (individuals, mother trees (families), populations) to evaluate its potential to respond to changing climatic conditions. Location Europe. Time Period 2016–2019. Major Taxa Studied European beech ( Fagus sylvatica L.). Methods We conducted a fully reciprocal transplantation experiment with more than 9000 beech seeds from seven populations across a Europe‐wide gradient. We compared morphological (Specific Leaf Area), phenological (leaf unfolding) and fitness‐related (growth, survival) traits across various biological scales: within single mother trees, within populations and across different populations under the contrasting climates of the translocation sites. Results The experiment revealed significant phenotypic variation within the offspring of each mother tree, regardless of geographic origin. Initially, seedling height growth varied among mother trees and populations, likely due to maternal effects. However, the growth performance successively aligned after the first year. In summary, we observed a consistent growth response in different beech populations to diverse environments after initial maternal effects. Main Conclusions The study strikingly demonstrates the importance of considering intraspecific variation. Given the surprisingly broad spectrum of phenotypes each mother tree holds within its juvenile offspring, we conclude that Fagus sylvatica might have the potential for medium‐term population persistence in face of climate change, provided that this pattern persists into later life stages. Hence, we also suggest further investigating the inclusion of passive adaptation and natural dynamics in the adaptive management of forests.